Tunable regulatory activities of 1, 10-phenanthroline derivatives towards acid sphingomyelinase and Zn(ii)–amyloid-β. Issue 42 (1st May 2019) - Yi, Yelim; Han, Jiyeon; Park, Min Hee; Park, Nahye; Nam, Eunju; Jin, Hee Kyung; Bae, Jae-sung; Lim, Mi Hee
Abstract : A novel series of 1, 10-phenanthroline (phen) derivatives capable of regulating acid sphingomyelinase, Zn(ii )-bound amyloid-β, or both was rationally designed. Abstract : We report a new series of small molecules able to achieve the tunability of modulatory activities against acid sphingomyelinase (ASM) and Zn(ii )-bound amyloid-β [Zn(ii )–Aβ], two pathological targets found in the brain affected by Alzheimer's disease. Rational tuning of the hydrophobicity and Zn(ii ) binding affinity of the 1, 10-phenanthroline (phen ) framework successfully yielded compounds as chemical modulators for ASM (4 and5 ), Zn(ii )–Aβ (phen, 1, and2 ), or both (3 ).